Coastal oceanographic conditions during a cold front passage over a fish spawning aggregation site located in the Mesoamerican Reef. (30th September 2022) - Sánchez-Hernández, Suleyma; Carrillo, Laura; Heyman, William D.
Abstract: In this study, an observational campaign that included measurements of coastal currents and thermohaline structure on a fish aggregation reef site during 11–17 March 2017 is analyzed. For the period of the present study, we observed the response of the coastal oceanographic conditions to meteorological forcing. In particular, we described the effects of the cold front passage (locally called a " Norte") on the water column over a fish aggregation reef site. Before the passage of the Norte, the site was exposed to NE - SE Trade winds, stratification of the water column and sea surface currents moved mainly northward in the alongshore component and offshore in the cross-shore component. However, during the passage of the cold front or Norte, there were changes in the wind field, temperature and atmospheric pressure. Norte conditions were associated with strong northerly winds and with a continuous drop in air temperature. This atmospheric forcing resulted in an evolution of the oceanographic conditions at the reef site from that observed during Trade winds. It changed from stratified to a well-mixed water column, and then dense water on the shallow reef area resulted by cooling and evaporation due to the extreme weather condition during Nortes . This dense water descends down the inner-shelf with density contrast of 0.52 kg/m 3 producing a near bottom offshore flow (below 15 m depth). Thus, weather conditions have a determinant role in coastal currents and in the thermohaline structure in the fish aggregation reef site. Highlights: Rapid respond of coastal oceanographic conditions to meteorological forcing. Well-mixed water column, southward and onshore flow resulted after the cold front. Over the shelf, near bottom dense offshore flow was observed. Determinant role of reef lagoon on inner shelf thermohaline structure.